Architecture through Drawing (diségno, 2023)
The act of drawing has long been the foundational stone for architectural expression. Through the chaotic lines on a canvas, we can understand exaptation as a unique path to diversify architectural drawing frameworks, moving towards environmentally-conscious perspectives. [read more]